ANALISIS TERHADAP BIDANG USAHA PERTANIAN PADA DISPERINDAG KABUPATEN BENER MERIAH MELALUI MODEL BISNIS KANVAS: Indonesia - Musdhalipah; Fauzi, Achmad (Asosiasi Dosen Muda Indonesia, 2024)
This study focuses on the regional trade commodities in the district of Truly Merry, specifically agricultural products like coffee, tomatoes, and chilies. The community and the sustainable agricultural sector can sustain the renewal of products with improved labels, allowing agricultural products to be distributed on a national level and promoting the overall advancement of regional agriculture. The documented harvest achieved a remarkable coverage of 88% in this agency, surpassing agricultural outcomes in other locations. This approach employs qualitative methodologies that rely on foundational principles within the framework of a business model canvas. The objective of this concept is to establish the initial procedure in order to distribute it to different places and enhance people's income towards a prosperous Indonesia. The rise in agricultural production is backed by the appropriate OPD through engagement in enhancing business models, which will be further followed by considering fair distribution coverage. The ultimate outcomes of this study aim to furnish information literacy that can be utilized by organizations as supplementary data on agricultural items in genuinely thriving locations.